2014
DOI: 10.5271/sjweh.3469
|View full text |Cite
|
Sign up to set email alerts
|

Does workplace health promotion reach shift workers?

Abstract: This study is the first to propose the hypothesis that lack of workplace health promotion plays a role in the incidence of shift work-related health problems. Surprisingly, we found that shift work in general is not a risk factor for low availability of and participation in workplace health promotion. However, differences between subgroups of shift workers need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This claim is also supported in the literature as previous studies have found it difficult to recruit (especially) night workers for intervention studies (Nabe- Nielsen et al 2011;Garde et al 2012;Rasmussen et al 2014). Nevertheless, in contrast to this knowledge, not all studies within this research area support the hypothesis that shift workers are disadvantaged with respect to interventions initiated at the workplace (Nabe- Nielsen et al 2015;Oberlinner et al 2009;Ott et al 2010).…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…This claim is also supported in the literature as previous studies have found it difficult to recruit (especially) night workers for intervention studies (Nabe- Nielsen et al 2011;Garde et al 2012;Rasmussen et al 2014). Nevertheless, in contrast to this knowledge, not all studies within this research area support the hypothesis that shift workers are disadvantaged with respect to interventions initiated at the workplace (Nabe- Nielsen et al 2015;Oberlinner et al 2009;Ott et al 2010).…”
Section: Introductionsupporting
confidence: 50%
“…In the present study, we also found a lower self-reported participation in activities aimed at improving working methods and a lower self-reported participation in education or courses aimed at improving qualifications among shift workers. However, the literature investigating shift workers' participation in interventions is sparse (Robroek et al 2009) and divergent: One study reported a higher participation in medical examinations and health seminars among shift workers than among day workers (Oberlinner et al 2009;Ott et al 2010), one study did not find systematic differences between day workers' and shift workers' participation in workplace health promotion (Nabe- Nielsen et al 2015), and two studies reported a lower participation in workplace interventions among shift workers (Henritze et al 1992;Rasmussen et al 2014). The differences between the results of these studies may be due to differences in design (e.g., intervention studies vs. observational studies), content of the intervention (e.g., working environment interventions vs. health promotion), comprehensiveness of the interventions (e.g., short information meetings vs. a large-scale participatory approach), and study population (e.g., the general working population, eldercare workers, or industrial workers).…”
Section: Comparison With Previous Studiesmentioning
confidence: 97%
“…Data on the work environment and health in the study population were obtained from the 2010 round of the Danish Work Environment Cohort Study (DWECS). 17 20 This study consists of questionnaires assessing work environment and health in the general working population of Denmark, and has been repeated every five years since 1990. The questions used for this study are specified below.…”
Section: Methodsmentioning
confidence: 99%
“…The questions on pain and use of pain medication are specified below. A total of 10,605 workers (∼53%) replied to 2010 questionnaire [Nabe‐Nielsen et al, ]. For the present analyses, we included only currently employed wage earners who were not on long‐term sick leave (N = 10,024).…”
Section: Methodsmentioning
confidence: 99%